Finding Functional Differences Between Species in a Microbial Community: Case Studies in Wine Fermentation and Kefir Culture - Melkonian, Chrats; Gottstein, Willi; Blasche, Sonja; Kim, Yongkyu; Abel-Kistrup, Martin; Swiegers, Hentie; Saerens, Sofie; Edwards, Nathalia; Patil, Kiran R.; Teusink, Bas; Molenaar, Douwe (Frontiers in Microbiology, 2019)
Microbial life usually takes place in a community where individuals interact, by competition for nutrients, cross-feeding, inhibition by end-products, but also by their spatial distribution. Lactic acid bacteria (LAB) are prominent members of microbial communities responsible for food fermentations. Their niche in a community depends on their own properties as well as those of the other species. Here, we apply a computational approach, which uses only genomic and metagenomic information and functional annotation of genes, to find properties that distinguish a species from others in the community, as well as to follow individual species in a community. We analysed isolated and sequenced strains from a kefir community, and metagenomes from wine fermentations. We demonstrate how the distinguishing properties of an organism lead to experimentally testable hypotheses concerning the niche and the interactions with other species. We observe, for example, that L. kefiranofaciens, a dominant organism in kefir, stands out among the Lactobacilli because it potentially has more amino acid auxotrophies. Using metagenomic analysis of industrial wine fermentations we investigate the role of an inoculated L. plantarum in malolactic fermentation. We observed that L. plantarum thrives better on white than on red wine fermentations. We provide experimental support for the hypothesis that this is most likely caused by growth-inhibiting compounds in grape skins present in red wine fermentations.